Foodgrain consumption and calorie intake patterns in Ethiopia - Berhane, Guush; Paulos, Zelekawork; Tafere, Kibrom; Tamru, Seneshaw (International Food Policy Research Institute, 2011)
Levels and composition of food consumption are major determinants of the nutritional wellbeing of individuals, which in turn, have important implications for health, productivity, and income. Analyzing food consumption patterns in poor countries, such as Ethiopia, is therefore pivotal to designing national policies to promote food security.Food consumption patterns in Ethiopia are diverse, and unlike in many other countries, no single crop dominates the national food basket (e.g., rice in most of East Asia, maize in Latin America, or cassava in Central Africa). The Ethiopian food basket consists of a wide variety of grains and other staples. However, consumption levels and mixes of these grains vary widely according to differences in agro-ecology, socioeconomic levels, and livelihood strategies. Moreover, given dependence on own production, particularly in rural areas, foodgrain consumption varies at different times of the year. As in many other traditional societies, dietary preferences and consumption patterns are heavily influenced by cultural values and traditions and may not necessarily reflect availability or the nutritional quality of specific food items.